2010
DOI: 10.1159/000322083
|View full text |Cite
|
Sign up to set email alerts
|

Use and Effect of Vasopressors after Pediatric Traumatic Brain Injury

Abstract: Background: Vasopressors are commonly used to increase mean arterial blood pressure (MAP) and cerebral perfusion pressure (CPP) after traumatic brain injury (TBI), but there are few data comparing vasopressor effectiveness after pediatric TBI. Objective: To determine which vasopressor is most effective at increasing MAP and CPP in children with moderate-to-severe TBI. Methods: After institutional review board approval, we performed a retrospective cohort study of children 0–17 years old admitted to a level 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 61 publications
4
33
0
1
Order By: Relevance
“…27 The results of that study were remarkably similar to that observed with NE; Phe and NE prevented impairment of autoregulation in the newborn female via blockade of ERK MAPK upregulation, but these same agents did not do so in newborn males where it augmented ERK MAPK upregulation. 17,19 In the present study, we observed that NE prevented impairment of autoregulation in juvenile male and female pigs due to blockade of ERK MAPK upregulation, indicating that for this vasoactive agent outcome is dependent on both age and sex.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…27 The results of that study were remarkably similar to that observed with NE; Phe and NE prevented impairment of autoregulation in the newborn female via blockade of ERK MAPK upregulation, but these same agents did not do so in newborn males where it augmented ERK MAPK upregulation. 17,19 In the present study, we observed that NE prevented impairment of autoregulation in juvenile male and female pigs due to blockade of ERK MAPK upregulation, indicating that for this vasoactive agent outcome is dependent on both age and sex.…”
Section: Discussionsupporting
confidence: 70%
“…7 Cerebral autoregulation is impaired to a greater extent in newborn compared with juvenile pigs, which parallels that observed clinically. 4,8 Current 2012 Pediatric Guidelines recommend maintaining CPP above 40 mm Hg in children and adolescents with severe TBI, noting that an age-related continuum for the optimal CPP is between 40 and 65 mm Hg. 9,10 Maintaining CPP within these levels is often managed by use of vasoactive agents to increase CPP and optimize CBF.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Here, we analyzed the e®ects of adrenaline on cerebral venous circulation in newborn and adult rats in normal state and after stroke development. Our results showed that adrenaline caused the constrictor e®ect on the sagittal sinus in healthy animals without any age di®erences.…”
Section: Discussionmentioning
confidence: 99%
“…25 Adrenaline caused vasoconstriction of cerebral vessels in healthy rats but did not induce any changes in the CBF in rats with intracranial hemorrhages, probably due to decrease in the BBB permeability. 13 Here, we proposed adrenaline test as additional indirect method to the study of BBB permeability as well as to determine e®ectiveness of adrenaline as a main course in therapy of stroke [27][28][29] in neonates and adults.…”
Section: The Study Of Bbb Permeabilitymentioning
confidence: 99%
“…30 Notice, there is limited information regarding the age particularities of adrenergic control of cerebral circulation. 26,30 There are a lot of techniques providing CBF imaging. The most accepted are positron emission tomography (PET), 31,32 magnetic resonance imaging (MRI) (including functional MRI), 33À36 Doppler ultrasound and near-infrared spectroscopy (NIRS).…”
Section: à11mentioning
confidence: 99%